Adubação nitrogenada em clones de batata-doce : comportamento agronômico, bioquímico e uso do nutriente pela planta - Santos Neto, Antônio Rosalvo dos (2013)
Due to the need to define a dose of nitrogen agronomic and economically suitable for the cultivation of sweet potato in the state of Sergipe. The aim of this study was to evaluate the root yield, starch and ethanol in sweet potato clones analyzed from nitrogen. The study was conducted between the months of March and August 2012 at the Experimental Farm |Campus Rural da UFS|, located in the municipality of São Cristóvão, Sergipe, Brazil. We used a randomized complete block randomized in a 5x3 factorial design with three replications, testing five N rates (0, 30, 60, 120 and 240 kg ha-1), using as a source of N as urea (45 % N), and three clones of sweet potato (Brazlândia Branca, IPB-075 and IPB-149). The commercial cultivar Brazlândia Branca was considered as a witness. The crop was harvested at 150 days after planting, by quantifying the total biomass productivity and roots, the dry matter content of the roots, the total dry mass and root biomass, nitrogen content in biomass and roots, the crude protein content in biomass and roots, the accumulation of nitrogen in the biomass of shoots and roots, harvest index, physiological efficiency, efficiency in production of tuberous roots, the recovery efficiency of the utilization efficiency nitrogen, starch content, the starch and yield of ethanol. All clones in this study reached values higher than the national average yield of root yield (11,84 Mg ha-1). The productivity of the aboveground biomass of clones, respond to levels above the levels of nitrogen applied in the present study. A dose of approximately 130 kg ha-1 nitrogen provides maximum yields of total productivity of the tuberous roots of sweet potato clones. The physiological efficiency of recovery of nitrogen applied to the N utilization and efficiency of storage root production decreased with increasing doses of N applied to all sweet potato clones evaluated, whereas the accumulation of N in shoots and tuberous roots of clones IPB-149 and IPB-075 showed significant increases. The dose of 154 kg ha-1 N promotes greater production of total dry matter in storage roots of sweet potato clones. Clone sweet potato IPB-149 showed higher correlation between the use of nitrogen and root yield. With a dose between 120 and 210 kg ha-1 of nitrogen as urea can obtain maximum yields of starch and ethanol in the culture of sweet potato.